Evaluating the effectiveness of learning ear anatomy using holographic models - Joshua J. Gnanasegaram; Regina Leung; Jason A. Beyea (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Computer-assisted learning has been shown to be an effective means of teaching anatomy, with 3-D visualization technology more successfully improving participants’ factual and spatial knowledge in comparison to traditional methods. To date, however, the effectiveness of teaching ear anatomy using 3-D holographic technology has not been studied. The present study aimed to evaluate the feasibility and effectiveness of learning ear anatomy using a holographic (HG) anatomic model in comparison to didactic lecture (DL) and a computer module (CM). Methods A 3-D anatomic model of the middle and inner ear was created and displayed using presentation slides in a lecture, computer module, or via the Microsoft HoloLens. Twenty-nine medical students were randomized to one of the three interventions. All participants underwent assessment of baseline knowledge of ear anatomy. Immediately following each intervention, testing was repeated along with completion of a satisfaction survey. Results Baseline test scores did not differ across intervention groups. All groups showed an improvement in anatomic knowledge post-intervention (p < 0.001); the improvement was equal across all interventions (p = 0.06). Participants rated the interventions equally for delivery of factual content (p = 0.96), but rated the HG higher than the DL and CM for overall effectiveness, ability to convey spatial relationships, and for learner engagement and motivation (p < 0.001). Conclusions These results suggest that 3-D holographic technology is an effective method of teaching ear anatomy as compared to DLs and CMs. Furthermore, it is better at engaging and motivating learners compared to traditional methods, meriting its inclusion as a tool in undergraduate medical education curriculum.